Does Technological Environment Interact with Social Capital and Cooperative Society’s Performance in Nigeria? - Egwakhe, J. A; Dada, O. A.; Onu C. A.; Umukoro, J. E. (Journal of Strategic Management, 2024)
Purpose: Debate on cooperative society's performance has remained unabated for stakeholders since it is closer to the grassroots. Moreover, the influence of social capital has shown divergent outcomes. Nevertheless, the environment in which businesses operate is core. Therefore, this paper argues that social capital effect on cooperative societies' performance is significantly moderated by technological environment. Materials and Methods: A cross-sectional survey research design was used in collecting data from 361 executives of cooperative societies operating in Ogun State, Nigeria, selected through the stratified sampling technique. Also conducted were the reliability and validity tests on the adapted questionnaire before utilizing it for this study. Findings: The hierarchical regression analysis results revealed that social capital effect on cooperative societies performance in Ogun State, Nigeria, was negative and not significantly moderated by the technological environment (Î²= -0.016, t= -1.456, âˆ†R2 = 0.001, âˆ†F= 2.120, p>0.05). Implications to Theory, Practice and Policy: Since, statistically, the technological environment had a negative and insignificant effect strengthens the report by the AU Inter-Africa Information System and African Union Commission on Cooperatives, and thus, the need for executives of cooperative societies in Nigeria to invest in technology is germane because a business lagging in technology in this present era and business climate will gradually but surely not survive.